Weed Management in Organic Farming - Kanta Behera, Shishir; Nanda, Sankarshan (International Journal of Psychosocial Rehabilitation, 2025)
Weeds are one of the key obstacles for sustaining the productivity of the crop. Weeds fight with crops for soil moisture, nutrients, space, and solar radiation; and decrease the quality and yield of produce. In addition, they also act as an alternative host for disease-causing microorganisms and insectpests. Problems with weeds vary in various seasons, crops, management practices, and agro-ecological conditions. Various methods of weed control in field crops are used with varying degrees of success, including preventive, chemical biological, cultural, mechanical and biotechnological approaches. Chemical intervention in organic farming systems is not permitted because of the lack of research on non-chemical weed management options has made weeds serious trouble in organic farming. It is important to understand that weeds will never be eliminated under an organic scheme, but will only be managed. In organic systems, weed control focuses on management techniques that are designed to prevent weeds, as well as crop production that is large enough to out-compete weeds and reduce the availability of weed resources. In organic farming, the main target of weed management is to bring about substantial yield improvement of the crop and to decrease the degree of direct control inputs.